Navigating Ethical and Strategic Challenges in Public-Private Partnerships: Balancing Public Welfare and Private Profit - Al-Murisi, Yunes Mohammed Muthanna; Ibrahim, Adil Hassan; Corr, Ousman (Universitas Bojonegoro, 2025)
This study explores the ethical and strategic dynamics of Public-Private Partnerships (PPPs), focusing on the balance between public welfare and private profit. Through a comprehensive literature review, the research identifies key challenges, including accessibility, affordability, and governance deficiencies. While successful PPP projects, such as Chile’s toll roads and South Africa’s Gautrain rail system, demonstrate the potential for inclusive and efficient outcomes, failures like the Cochabamba water crisis highlight the risks of prioritizing profitability over equity and transparency. The findings emphasize that effective governance frameworks, transparent contracts, and stakeholder engagement are critical for aligning PPP objectives with public interest. The study also identifies a research gap in developing adaptive governance models that integrate affordability and inclusivity without undermining financial sustainability. Recommendations include capacity-building within public institutions, innovative risk-sharing mechanisms, and enhanced public oversight. Future research should focus on longitudinal assessments of PPPs to evaluate their long-term impacts on both public welfare and private sector viability. By addressing these challenges, PPPs can evolve into equitable and effective tools for infrastructure development and service delivery. This study contributes to the ongoing discourse in public.